PID-Based Temperature Control Device For Electric Kettle - Nor Shah, Mohd Badril; Zailan, Norfahaniza; Zainal Abidin, Amar Faiz; Mohd Ab Halim, Mohd Firdaus; Mohd Annuar, Khalil Azha; Azahar, Arman Hadi; Harun, Mohamad Haniff; Yaakub, Muhamad Faizal (Institute of Advanced Engineering and Science, 2019)
A normal electric kettle usually is intended to boil water until boiling point and cannot be controlled. Most of the kettle does not provide the temperature display for user to track the current temperature reading. Thus, this project is inspired from the shortcoming of most kettles that are sold at the market. By using Arduino microcontroller, a device is developed to control water temperature inside electric kettle. To provide automated temperature control, PID controller is chosen since it can provides precise water temperature control with less fluctuation. The device is also equipped with the display of the current water temperature and desired temperature. The device is tested to an electric kettle and the performance of PID controller in controlling water temperature is compared to on-off controller. An analysis is performed based on the amount of fluctuation with respect to desired temperature to verify the efficacy of the designed circuit and controller. It is found that the developed device and PID controller are capable to control the water temperature inside kettle based on the desired temperature set by user with less amount of fluctuation.